Multidate, multisensor remote sensing reveals high density of carbon‐rich mountain peatlands in the páramo of Ecuador. (26th July 2017) - Hribljan, John A.; Suarez, Esteban; Bourgeau‐Chavez, Laura; Endres, Sarah; Lilleskov, Erik A.; Chimbolema, Segundo; Wayson, Craig; Serocki, Eleanor; Chimner, Rodney A.
Abstract: Tropical peatlands store a significant portion of the global soil carbon (C) pool. However, tropical mountain peatlands contain extensive peat soils that have yet to be mapped or included in global C estimates. This lack of data hinders our ability to inform policy and apply sustainable management practices to these peatlands that are experiencing unprecedented high rates of land use and land cover change. Rapid large‐scale mapping activities are urgently needed to quantify tropical wetland extent and rate of degradation. We tested a combination of multidate, multisensor radar and optical imagery (Landsat TM/PALSAR/RADARSAT‐1/TPI image stack) for detecting peatlands in a 2715 km 2 area in the high elevation mountains of the Ecuadorian páramo. The map was combined with an extensive soil coring data set to produce the first estimate of regional peatland soil C storage in the páramo. Our map displayed a high coverage of peatlands (614 km 2 ) containing an estimated 128.2 ± 9.1 Tg of peatland belowground soil C within the mapping area. Scaling‐up to the country level, páramo peatlands likely represent less than 1% of the total land area of Ecuador but could contain as much as 23% of the above‐ and belowground vegetation C stocks in Ecuadorian forests. These mapping approaches provide an essential methodological improvement applicable to mountain peatlands across the globe, facilitating mapping efforts in support of effective policy and sustainable management, including national and global C accounting and C management efforts. Abstract : Tropical mountain peatlands contain extensive peat soils that have yet to be mapped or included in global carbon estimates. Our map displayed a high coverage of peatlands containing large belowground soil carbon storage within the Ecuadorian Andes. These mapping approaches provide an essential methodological improvement applicable to mountain peatlands across the globe, facilitating mapping efforts in support of effective policy and sustainable management, including national and global carbon accounting and C management efforts.